Localization Operators and an Uncertainty Principle for the Discrete Short Time Fourier Transform - Carmen Fernández; Antonio Galbis; Josep Martínez (Abstract and Applied Analysis)
Localization operators in the discrete setting are used to obtain information on a signal f from the knowledge on the support of its short time Fourier transform. In particular, the extremal functions of the uncertainty principle for the discrete short time Fourier transform are characterized and their connection with functions that generate a time-frequency basis is studied.